2002
DOI: 10.2174/0929867024606777
|View full text |Cite
|
Sign up to set email alerts
|

Vinorelbine in the Treatment of Non-Small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) remains a fatal disease: the majority of patients are diagnosed as having metastases or advanced inoperable tumors. The activity of chemotherapy in NSCLC patients is low with objective response rarely complete and sustained. Cisplatin-based combinations are considered as the standard chemotherapy treatment. Recently., the introduction of new and less toxic chemotherapeutic agents., such as vinorelbine., has led investigators to research for active non-cisplatin-containing com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 66 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Although vinorelbine, like other vinca alkaloids, induces apoptosis of tumor cells [23] or arrests the cell cycle in G2/M phase [21] by inhibiting the assemblage of tubulin [24], vinorelbine has milder side effects compared to other vinca alkaloids [25,26]. Vinorelbine is applied clinically either alone or in combination with other drugs to treat breast cancer [24] and non-small cell lung cancer [27,28]. In this study, we analyzed signal transduction for vinorelbineinduced apoptosis in human T cell lymphoma, and found that Bid is cleaved by caspases-3 and -9 as well as by caspase-8.…”
Section: Introductionmentioning
confidence: 99%
“…Although vinorelbine, like other vinca alkaloids, induces apoptosis of tumor cells [23] or arrests the cell cycle in G2/M phase [21] by inhibiting the assemblage of tubulin [24], vinorelbine has milder side effects compared to other vinca alkaloids [25,26]. Vinorelbine is applied clinically either alone or in combination with other drugs to treat breast cancer [24] and non-small cell lung cancer [27,28]. In this study, we analyzed signal transduction for vinorelbineinduced apoptosis in human T cell lymphoma, and found that Bid is cleaved by caspases-3 and -9 as well as by caspase-8.…”
Section: Introductionmentioning
confidence: 99%
“…Vinorelbine (5Ј nor-anhydro-vinblastine) is a clinically approved drug that is frequently used in the treatment of various cancers, including metastatic breast cancer (Weber et al, 1995) and nonsmall-cell lung cancer (Gridelli and De Vivo, 2002). Vinorelbine is better tolerated than many of the other vinca alkaloids, including reduced neurotoxicity (Mathé and Reizenstein, 1985) due to its reduced affinity for axonal microtubules (Binet et al, 1990).…”
mentioning
confidence: 99%
“…2 Vinorelbine has been approved as a treatment for various cancers, including metastatic breast cancer and nonsmall cell lung cancer. 3,4 Vinorelbine is better tolerated than other vinca alkaloids because of a lower propensity for axonal microtubules to cause neurotoxicity. 5 Many studies have put effort into maintaining the vinorelbine concentration surrounding tumor cells in order to improve the anticancer activity of vinorelbine.…”
Section: Introductionmentioning
confidence: 99%